PENGARUH FREE CASH FLOW DAN FAKTOR-FAKTOR LAINNYA TERHADAP EARNINGS MANAGEMENT - Nurfaidilla , Aninda Okta; Susanti, Apit (E-Jurnal Akuntansi TSM, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of free cash flow, profitability, institutional ownership, leverage, board of commissioners, sales growth, and firm size on earnings management. This study used 74 manufacturing companies listed on the Indonesia Stock Exchange during period 2019 - 2021 as samples with a total sample data is 222 data. The sample selection process uses the purposive sampling method and uses the multiple regression method in testing hypotheses. The empirical evidence obtained regarding the results of this study shows that free cash flow, profitability, and leverage have an influence on earnings management. If the free cash flow, profitability, and leverage owned in a company are high, the level of earnings management is also high. In this study, the institutional ownership, board of commissioners, leverage and firm size had no influence on earnings management.